Exploratory findings from a prematurely closed international, multicentre, academic trial: RAVELLO, a phase III study of regorafenib versus placebo as maintenance therapy after first-line treatment in RAS wild-type metastatic colorectal cancer. Issue 4 (16th August 2019) - Cardone, Claudia; Martinelli, Erika; Troiani, Teresa; Sforza, Vincenzo; Avallone, Antonio; Nappi, Anna; Montesarchio, Vincenzo; Andreozzi, Francesca; Biglietto, Maria; Calabrese, Filomena; Bordonaro, Roberto; Cordio, Stefano; et al.
Abstract : Background: In patients with RAS wild-type (WT) metastatic colorectal cancer (mCRC), the role of maintenance therapy after first-line treatment with chemotherapy plus antiepidermal growth factor receptor (EGFR) monoclonal antibodies (MoAb) is still an object of debate. Methods: We assessed the efficacy and safety of regorafenib as a switch maintenance strategy after upfront 5-fluorouracil-based chemotherapy plus an anti-EGFR MoAb in patients with RAS WT mCRC. RAVELLO was a phase III, international, double-blind, placebo-controlled, academic trial. The primary endpoint was progression-free survival (PFS). Secondary endpoints included overall survival and toxicity. Regorafenib or placebo were administered daily for 3 weeks of 4-week cycle until disease progression or unacceptable toxicity, up to 24 months. Results: The study was stopped prematurely due to slow accrual and lack of funding after the randomisation of 21 patients: 11 in the regorafenib arm and 10 in the placebo arm. The small sample size precludes any statistical analysis. Toxicity was acceptable and consistent with the known regorafenib safety profile. Median PFS was similar in the two arms. However, a subgroup of patients treated with regorafenib experienced a remarkably long PFS. Three patients were progression free at 9 months in the regorafenib arm versus one patient in the placebo arm, whereas at 12 months two regorafenib-treated patients were still progression free versus none in the placebo arm. Conclusion: RAVELLO trial demonstrated that growing financial and bureaucratic hurdles affect the feasibility of independent academic research. Although stopped prematurely and within the limited sample size, RAVELLO suggests that regorafenib has not a major activity in maintenance setting after upfront chemotherapy and anti-EGFR MoAb. However, a subgroup of patients experienced a remarkable long PFS, indicating that a better refinement of the patient population would help to identify subjects that might benefit from a regorafenib personalised approach in the switch maintenance setting.